Electrodeposition of Ni–Fe–Mn/Al2O3 functionally graded nanocomposite coatings. (1st February 2017) - Torabinejad, V.; Aliofkhazraei, M.; Rouhaghdam, A. S.; Allahyarzadeh, M. H.
Abstract : In this study the Ni–Fe–Mn/Al2 O3 functionally graded (FG) coatings with thickness of 70 μm were fabricated onto mild steel substrates using pulse electrodeposition technique. Two types of FG coatings were deposited; the first type was synthesised through decreasing the pulse duty cycle gradually at a constant frequency and the second type was electrodeposited by increasing the frequency gradually at a constant duty cycle. The influences of pulse parameters including duty cycle and frequency on the microstructure, composition, microhardness corrosion and wear behaviour of electrodeposited FG nanocomposite coatings were evaluated. In the first type of coatings, Mn content was gradually decreased, also Fe and alumina contents changed in opposite directions. In the second type, chemical composition has not been affected through frequency alterations. The effect of frequency and duty cycle on the microhardness, corrosion and wear for different FG Ni–Fe–Mn/Al2 O3 nanocomposite coatings was investigated.